Professional occupation and income of graduates of a Graduate Program in Accounting (Revista Brasileira de Contabilidade e Gestão, 2016)
In recent years increased, in Brazil, the number of institutions accredited to offer courses stricto sensu, and such courses as they raise the level of knowledge and specialization of people tend to improve their employability and raise incomes. Thus, this study aims to identify and analyze the profile of professional occupation and income of graduates of the Graduate Program in Accounting from the Federal University of Santa Catarina. To meet the proposed objective, was elaborate a questionnaire, sent to all graduates of the program, getting 51 responses, representing 64.6% of total graduates from the program (Masters in Accounting). The results show that there was migration of activities performed by graduates, already that before joining the course the majority (82%) possessed the main professional activity linked to the market and upon completion of the master's most (54%) began to exert activity connected the academy. It was observed that 27% of masters initiated the course for a doctorate and that 74% who did not initiate, intend to do so. Proceeds perceived by graduates were also leveraged upon completion of the master, corroborating the results of previous research.
Keywords: master's degree; human capital theory; accounting